Scooby-Doo! World of Mystery 9 Mexico - Aztec City - Craft Plus Publishing Ltd (De Agostini Uk Ltd, 2004)
The Aztec ghost is haunting the ruins of Aztec City!Can the gang discover his secret and stop the sacrifices?
Keywords: Juvenile literature-Fiction